Caffeic acid phenethyl ester alleviates 1,2-dichloroethane-induced toxic cerebral edema: central and peripheral mechanisms - Sun, Yue; Yin, Bo; He, Shubei; Miao, Luxin; Yang, Jinhan; Wang, Yan; Jin, Xiaoxia (Frontiers in Pharmacology, 2026)
Background1,2-Dichloroethane (1,2-DCE) is a widespread environmental contaminant as well as a frequent occupational hazard. Given that inflammation and oxidative stress are key mechanisms in 1,2-DCE-induced cerebral edema, we investigated the efficacy of caffeic acid phenethyl ester (CAPE), a natural anti-inflammatory and antioxidant agent known to protect blood-brain barrier (BBB) integrity, against this intoxication and explored its underlying mechanisms.MethodsStatic inhalation exposure was used to establish a mouse model of 1,2-DCE-induced toxic cerebral edema. Cerebral edema was evaluated based on brain water content, histopathological changes, and tight junction proteins (TJPs) expression. The related anti-inflammatory and antioxidant mechanisms were analyzed by examining the p38 mitogen-activated protein kinase (p38 MAPK) and nuclear factor erythroid 2-related factor 2 (Nrf2) pathways, respectively. Additionally, the levels of specific cytokines and oxidative stress markers were quantified in both brain tissue and serum.ResultsCAPE alleviated the body weight loss and reduced the brain water content in 1,2-DCE-intoxicated mice. Hematoxylin and eosin (HE) staining revealed that CAPE effectively ameliorated the characteristic pathological manifestations of brain edema. CAPE mediated its protective effects through the downregulation of both the p38 MAPK and Nrf2 signaling pathways, resulting in suppressed expression of the cytokines tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β), and matrix metalloproteinase-9 (MMP-9), normalized levels of glutathione (GSH) and malondialdehyde (MDA), and attenuated loss of the TJPs Occludin and ZO-1. Furthermore, CAPE reversed the 1,2-DCE-induced alterations in pro-inflammatory cytokines and oxidative stress markers in peripheral serum, while inhibiting the expression of vascular cell adhesion molecule-1 (VCAM-1) and intercellular adhesion molecule-1 (ICAM-1) in brain tissue.ConclusionThis study provides the first evidence that CAPE effectively alleviates cerebral edema through mitigating both peripheral and central inflammatory responses and oxidative stress induced by 1,2-DCE.